Beyond Decadence Exposing the Narrative Irony in Jan Opolský's Prose - Butler, Peter (Karolinum, 2015)
Jan Opolsky has long been considered to be little more than an epigon of the Czech Decadence. By detailed analysis of his prose, this book aims to show that Opolsky is a master of sustained narrative irony and an accomplished writer in his own right. Introduction brings an overview of Czech Decadent/Symbolist literature and art in an European perspective. The first monograph evaluates archival sources, private correspondence with other literary figures and includes classified bibliography of Opolsky.
Keywords: Literární věda